The Influence of W-DLC and CrxN Thin Film Coatings on Impact Damage between Bearing Materials. Issue 6 (1st November 2016) - Dougherty, Patrick S. M.; Marinack, Martin C.; Patil, Deepak; Evans, Ryan D.; Higgs, C. Fred
ABSTRACT: In this work, the effect of hard tribological coatings was studied in terms of mitigating impact damage between tungsten carbide spherical elements and two different types of steel substrates. The coatings included a hard, highly elastic Tungsten-incorporated diamond-like carbon (W-DLC) coating at two different thicknesses and a harder, less elastic Crx N coating. Impacts were created using a drop-test rig described herein and characterized in three ways: a measure of the coefficient of restitution during impact, investigation of the impact site using an optical interferometer, and fixed ion beam cross sections of select impacts for observation of subsurface damage within the coating and substrate. It was found that hard coatings on softer substrates such as 440C steel were able to mitigate surface damage up to a certain impact speed, depending on the coating, but were unable to influence the coefficient of restitution. On harder substrates like 52100 alloy steel, the coatings were found to increase the coefficient of restitution, indicating a reduction in energy loss due to plastic deformation, and to reduce damage at each tested speed. These effects and their potential influence on bearing performance are discussed in regard to impact mechanics, surface metrology, and the material properties of the coating and substrate acquired by nanoindentation.